Language as a Source of Liberation, and Language as a Source of Control - Jonathan Luxmoore (Language, Culture, Politics)
We think and act through language. It determines how we exchange ideas, express emotions and see the world. And as such, language has always been a motor for enlightenment and progress, but also a means of control. It expresses our identity, and that identity takes multiple forms, affecting and shaping our values and priorities, how we view the world and those around us. They also determine the language we use - and this, not surprisingly, often becomes a source of political, social, cultural and ideological struggle.